2004
DOI: 10.1152/ajpgi.00358.2003
|View full text |Cite
|
Sign up to set email alerts
|

Delayed stress-induced colonic hypersensitivity in male Wistar rats: role of neurokinin-1 and corticotropin-releasing factor-1 receptors

Abstract: The mechanism(s) underlying stress-induced colonic hypersensitivity (SICH) are incompletely understood. Our aims were to assess the acute and delayed (24 h) effect of water avoidance (WA) stress on visceral nociception in awake male Wistar rats and to evaluate the role of two stress-related modulation systems: the substance P/neurokinin-1 receptor (SP/NK(1)R) and the corticotropin-releasing factor (CRF)/CRF(1) receptor (CRF/CRF(1)R) systems, as well as the possible involvement of the sympathetic nervous system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 45 publications
6
86
1
Order By: Relevance
“…A number of studies suggest that the CRF system might also be modulating visceral sensitivity related to stress [12,13,14,37]. With regard to the bladder, CRF is abundantly expressed in areas involved in the control of micturition (i.e., Barrington's nucleus, lumbosacral areas of the spinal cord) and administration of various CRF receptor agonists and antagonists alters cystometric parameters [38,39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies suggest that the CRF system might also be modulating visceral sensitivity related to stress [12,13,14,37]. With regard to the bladder, CRF is abundantly expressed in areas involved in the control of micturition (i.e., Barrington's nucleus, lumbosacral areas of the spinal cord) and administration of various CRF receptor agonists and antagonists alters cystometric parameters [38,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…A number of laboratory studies have demonstrated SIH to colorectal stimulation [10,11,12,13,14], and rats that are genetically predisposed to enhanced levels of anxiety exhibit exaggerated responses to colorectal distension [15]. In contrast, few laboratory reports exist about the relationship between stress and hypersensitivity of the urinary bladder.…”
Section: Introductionmentioning
confidence: 99%
“…Rats were deeply anesthetized with pentobarbital sodium (45 mg/kg ip, Nembutal; Abbott Laboratories, North Chicago, IL) and equipped with electrodes (Teflon-coated stainless steel wire; AstraZeneca, Mölndal, Sweden) implanted into the external oblique musculature, just superior to the inguinal ligament, as previously described (8,46). Electrode leads were then tunneled subcutaneously and externalized laterally (left abdominal side) for future access through a plastic fistula (AstraZeneca).…”
Section: Surgery: Implantation Of Electrodes For Electromyography (Emg)mentioning
confidence: 99%
“…The EMG activity was rectified, and the increase in the area under the curve of EMG amplitude (during each CRD pulse) over baseline (before CRD) was recorded as the response to distension. The same procedures have been previously used to assess pain-related responses to CRD in rats (8,46).…”
Section: Surgery: Implantation Of Electrodes For Electromyography (Emg)mentioning
confidence: 99%
See 1 more Smart Citation